Assessment of mating behaviour associated with fertility in Boer bucks - Wan Hamat, Nik Siti Mariani; Yaakub, Halimatun; Sithambaram, Shanmugavelu (Malaysian Society of Animal Production, 2011)
A study on the mating behavior of Boer bucks using the serving capacity test was conducted. Ten healthy Boer bucks with no previous experience of sexual activity were randomly selected and kept in individual pens. Each buck was allowed to mate naturally with a restrained female in oestrus for 30 minutes. Data on the serving capacity test were collected every 2 weeks for 5 consecutive weeks. All occurrences of mount attempts, mounts with and without ejaculation and the frequency of each event occurred were recorded. Latency to first mount and first ejaculation and refractory period were calculated. Buck efficiency was calculated by dividing the total number of ejaculations by the total number of mounts with and without ejaculation. Results showed that there were significant differences (P<0.05) between weeks for the mean latency to first mount, number of mounts and mount attempts, latency to first ejaculation, refractory period, number of ejaculations and mating efficiency. The number of ejaculations and mating efficiency increased in the beginning of the study. It was noted that experience had a decisive effect on the ability of bucks to properly mount and successfully ejaculate. Sexual experience might have provided the opportunity for bucks to learn and recognize important behavioural cues from the females.